Tarekat Naqsyabandiyah Khalidiyah Tanjung Pauh, Jitra, Kedah : Satu Kaedah Tazkiyat Al-Nafs - Mustafa Kamil, Hj. Ramli (2000)
The study is done to assess the position of the Tarekat Tasawuf order from the Islamic point of view, with special interest on Tarekat Naqsyabandiyah Khalidiyah of their religious centre in Tanjung Pauh, Jitra, Kedah. This discussion basically, centres on the concept of ‘Murid', 'Syeikh' and 'chains'of tutelage (salasilah), basic principles (doctrines) and their practices. The yardstick for this analysis is based on The Resolution of The Tarekat Tasawuf by JAKIM. The resolution is based on the al-Quran, al-Hadis, al-Ijmak, al-Qiyas and certain method or accepted principles of the members of Sunnah wa Jamaah. This tarekat provides way for the Moslem to tazkiyat al-rafs (performself spritual cleansing). The mechanism for self education of the tazkiyat al-nafs is through the zikir which is done according to precribed stage. The discussion starts by explaining the various divisions of tasawuf and the definations of 'tarekat' and ‘tasawuf'. In addition, the discussion is about several important aspects of Tarekat Naqsyabandiyah Khalidiyah. Some of these aspects include a brief history of Tarekat Naqsyabandiyah which discusses its formation and evolution and the spread of influence of the same Tarekat to Tanjung Pauh, Jitra, Kedah. This is followed by discussion of Tarekat Naqsyabandiyah Khalidiyah in Tanjung Pauh, Jitra, Kedah, in terms of its establishment, the background of its leaders and its practices bai'ah, talqin zikir, tawassul, khatam khawajakan, tawajjuh, tahlil, scripture studies and solitude programmes (Khalwat/Suluk). At the end of the study, comments and conclusions are made. The conclusion stresses that Tarekat Naqsyabandiyah Khalidiyah, in Tanjung Pauh, Jitra, Kedah is a true tarekat is based on true Islamic faith with the aim of tazkiyat al-nafs and achieving the ideal of Islam, Iman and Ihsan.